Asiaticoside inhibits renal fibrosis development by regulating the miR‐142‐5p/ACTN4 axis. (25th February 2021) - Zhang, Min; Liu, Shuhuan; Fang, Liming; Wang, Gang; Yin, Liping
Abstract: Renal fibrosis results in the progressive renal dysfunction and leads to chronic kidney disease (CKD) and ultimately end‐stage renal disease. Asiaticoside was reported to regulate synaptopodin, desmin, nephrin, and podocin levels in adriamycin‐induced nephropathy of rats. In this study, we found out that asiaticoside inhibited renal fibrosis in vitro and in vivo. Additionally, miR‐142‐5p was upregulated in in vitro and in vivo models of CKD. MiR‐142‐5p promoted the levels of collagen‐I, collagen‐IV, and fibronectin proteins. Additionally, miR‐142‐5p overexpression partly rescued the protective effect of asiaticoside on renal fibrosis. Mechanistically, miR‐142‐5p inhibited ACTN4 levels by binding with its 3´untranslated region, and further reduced its translation. Treatment of asiaticoside decreased miR‐142‐5p levels and increased ACTN4 levels. Rescue assays revealed that ACTN4 overexpression partially rescued the effect of miR‐142‐5p on renal fibrosis. Asiaticoside mitigated renal fibrosis by regulating the miR‐142‐5p/ACTN4 axis. In conclusion, asiaticoside inhibits renal fibrosis by regulating the miR‐142‐5p/ACTN4 axis. This novel discovery suggested that asiaticoside may serve as a potential medicine for renal fibrosis improvement. Abstract : Asiaticoside inhibits renal fibrosis in 5/6 Nx rats, and suppresses inflammatory response and the EMT process in TGF‐β‐treated NRK‐52E cells. Mechanistically, miR‐142‐5p binds to 3´UTR of ACTN4 mRNA, and further reduces its expression at the mRNA and protein levels. Asiaticoside decreases miR‐142‐5p levels to increase ACTN4 levels. ACTN4 rescues the promotive effects of miR‐142‐5p on inflammatory response and the EMT process of TGF‐β‐treated NRK‐52E cells.